2021
DOI: 10.1002/1873-3468.14145
|View full text |Cite
|
Sign up to set email alerts
|

The RNA demethylase ALKBH5 promotes osteoblast differentiation by modulating Runx2 mRNA stability

Abstract: AlkB homolog 5 (ALKBH5) has been reported as a key m6A demethylase that is involved in development and diseases; however, the function of ALKBH5 in osteogenesis remains unknown. In this study, we report that ALKBH5 mRNA and protein expression were upregulated during osteoblast differentiation and that ALKBH5 knockdown suppressed osteoblast differentiation, mineralization, and the expression of osteogenic biomarkers. Conversely, ALKBH5 overexpression promoted osteogenesis. Moreover, the expression of wild‐type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Furthermore, our study revealed that H205 is the conserved site of Alkbh5 for RNA demethylase activity in rats, and the mutation of H205A almost completely diminished the m6A modification activity. Similar result were observed for Alkbh5-induced osteoblast differentiation (Feng et al ., 2021), in which the H204A mutation in human Alkbh5 resulted in a complete loss of m6A modification activity (Feng et al, 2014; Zheng et al ., 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study revealed that H205 is the conserved site of Alkbh5 for RNA demethylase activity in rats, and the mutation of H205A almost completely diminished the m6A modification activity. Similar result were observed for Alkbh5-induced osteoblast differentiation (Feng et al ., 2021), in which the H204A mutation in human Alkbh5 resulted in a complete loss of m6A modification activity (Feng et al, 2014; Zheng et al ., 2013).…”
Section: Discussionsupporting
confidence: 89%
“…ALKBH5 is a well-known m 6 A demethylase which has extensive involvement in important biological processes ( Geula et al, 2015 ; Zhang et al, 2016 ). Recently, the roles of ALKBH5 in various biological processes have been confirmed, such as cell proliferation, tumor invasion and metastasis, and osteogenesis ( Shen et al, 2020 ; Wang et al, 2020 ; Feng et al, 2021 ; Li et al, 2021 ). Therefore, the current study investigated the role of ALKBH5 in the regulation of odontoblast differentiation by evaluating odontoblast differentiation in mDPC6T cells and in a mouse conditional Alkbh5 knockout model.…”
Section: Discussionmentioning
confidence: 99%
“…The ALKBH5-protein arginine N-methyltransferase six pathway affects the osteogenic differentiation of bone marrow mesenchymal stem cells ( Li et al, 2021 ). ALKBH5 promotes osteoblast differentiation by regulating the stability of RUNX2 mRNA ( Feng et al, 2021 ). Based on these findings, we hypothesized that m 6 A methylation may be involved in odontoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…ALKBH5 could also dynamically reverse the METTL3-induced m 6 A methylation, and coordinated with METTL3 to regulate osteogenic differentiation via NF-κB signaling ( Yu et al, 2020 ). Additionally, ALKBH5 promoted osteoblast differentiation through modulating Runx2 mRNA stability ( Feng et al, 2021 ). The m 6 A demethylase FTO also possesses a crucial role in BMSCs differentiation, the expression of which was improved during adipocyte differentiation whereas its expression was reduced during osteoblast differentiation, indicating FTO facilitated BMSCs to differentiate into adipocytes compared with osteoblasts ( Shen et al, 2018 ).…”
Section: The Role Of M 6 a In Ascsmentioning
confidence: 99%
“…2) The lineage-specific genes are closely associated with stem cells differentiation, which might be the targets of m 6 A modification to enable direct differentiation of stem cells into required lineages. For example, both the writer METTL3, and the erasers FTO and ALKBH5 can target the Runx2 mRNA of BMSCs to regulate osteogenesis, indicating the methylated level of Runx2 mRNA is pivotal for osteogenic differentiation ( Yan et al, 2020 ; Wang J. et al, 2021 ; Feng et al, 2021 ). However, more efforts are needed to determine the key genes associated with the cells differentiation and clarify the potential mechanisms.…”
Section: Problems and Pespectivesmentioning
confidence: 99%